Elusive Porn: Learning from Alastonsuomi - Paasonen, Susanna (United States, 2026)
This paper explores boundary work between pornography and other sexual media among the users of Alastonsuomi (“Naked Finland”), a Finnish-language image gallery dedicated to nudity and sexual self-expression. Building on 31 semi-structured in-depth interviews, it asks how, and in connection to what kinds of content the participants evoke the notion of porn in connection with sexual self-shooting. Within this, distinctions become drawn between different platforms, aesthetic qualities, as well as social and personal meanings.
Selected Papers of #AoIR2025: The 26th Annual Conference of the Association of Internet Researchers